Investigation of non-stationary characteristic of one class of singleserver service systems - Ivnitzky, V. (Lithuanian Mathematical Journal, 1972)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: В. А. Ивницкий. Исследование нестационарных характеристик одного класса однолинейных систем обслуживания V. Ivnickis. Vienos klasės vienatiesiniu aptarnavimo sistemų nestacionariniu charakteristikų tyrimas